Linking Ethical Leadership to Innovative Performance: The Role of Intellectual Capital in BUMDes Tourism Sector in Indonesia - Ahmad, Ahmad; Sariwulan, Rd. Tuty; Nikensari, Sri Indah (Program Studi S3 Ilmu Manajemen, 2024)
This study examines the role of ethical leadership in the innovative performance of employees in Village-Owned Enterprises (BUMDes). Furthermore, the purpose of the study is to investigate the mediating effects of human capital and social capital on the relationship between ethical leadership and employees’ innovative performance in the tourism sector of BUMDes in Indonesia. Primary data were collected from managerial-level employees of tourism-based BUMDes in Indonesia. Structural Equation Modelling (SEM) was employed to analyze the data and to identify both direct and indirect effects. The findings reveal a significant positive impact of ethical leadership on the innovative performance of BUMDes employees. In addition, ethical leadership was found to have both direct and indirect effects on innovative performance, with the indirect effect being mediated by intellectual capital (IC). The study highlights that IC and ethical leadership are critical resources in fostering a knowledge-driven culture and enhancing innovative performance among employees of BUMDes in the tourism sector. This research represents a novel attempt to explore the nexus between ethical leadership, IC, and innovative performance in the context of BUMDes in Indonesia. Moreover, it offers practical strategies for BUMDes managers to optimize business processes and promote innovative practices among employees, particularly within the rural tourism sector.